2020 Sensor Signal Processing for Defence Conference (SSPD) 2020
DOI: 10.1109/sspd47486.2020.9272170
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband Angle of Arrival Estimation Exploiting Graph Topology and Graph Signals

Abstract: Based on recent results of applying graph signal processing (GSP) to narrowband angle of arrival estimation for uniform linear arrays, we generalise the analysis to the case of arrays with elements placed arbitrarily in three dimensional space. We comment on the selection of the adjacency matrix, analyse how this new approach compares to the multiple signal classification (MUSIC) algorithm, and provide an efficient implementation. We demonstrate that the GSP approach can perform as well as the MUSIC algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…In this way, p(ω) becomes a special eigenvector t u of the adjacency matrix A(γ 0 , ω), which corresponds to the unit eigenvalue. It is worth noting that, compared with [10,11], only a spatial adjacency matrix is used. This is due to the fact that the temporal adjacency matrix requires a precise time shift, which is difficult to satisfy in the real underwater scenarios.…”
Section: Graph-based Mfp Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, p(ω) becomes a special eigenvector t u of the adjacency matrix A(γ 0 , ω), which corresponds to the unit eigenvalue. It is worth noting that, compared with [10,11], only a spatial adjacency matrix is used. This is due to the fact that the temporal adjacency matrix requires a precise time shift, which is difficult to satisfy in the real underwater scenarios.…”
Section: Graph-based Mfp Localizationmentioning
confidence: 99%
“…In [10], the authors build a cyclic graph structure in the spatial and temporal domains, such that the array signal becomes an eigenvector of the adjacency matrix corresponding to the unit eigenvalue. [11] further develops the approach by choosing a fully connected graph and highlighting the performance difference between the GSP and MUSIC methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graph signal processing uses a new data structure that studies the connection of things, which has shown excellent performance in many fields such as graph neural network and graph cuts [3]. Some related works can be found focusing on the use of graph signals to deal with DoA estimation problems in the radar array system [4][5][6], microphone and speakers [7,8], and the sonar array system [9]. Experiments show that the graph signal processing-based DoA methods have better performance than traditional algorithms such as Multiple Signal Classification (MUSIC) in a low signal-to-noise ratio environment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…where X ∈ C M×Q represent x(k) in (5), which is the snapshot signal samples collected by M receiving antennas; Σ = diag {σ i } I i=1 is the diagonal matrix of the RCS scattering coefficient of the far-field targets; W ∈ C M×Q is the sampling noise term of n(k) in Equation ( 5), usually additive white gaussian noise (AWGN). The receiving steering vector B includes the two-way phase delay, so the expression is the same as the steering vector st (θ i ,R i ,M) in Equation ( 4):…”
mentioning
confidence: 99%